Anti-depressant Activity of the Seeds of Zanthoxylum armatum on Swiss Albino Mice (Nepal Journal of Health Sciences, 2022)
Introduction: Depression disorder has significant potential morbidity and mortality, contributing to suicide, incidence and adverse outcomes of medical illness, disruption in interpersonal relationships, substance abuse, and lost work time.Objectives: The present study was designed to study the anti-depressant activity of the seeds extract of Zanthoxylum armatum using a forced swim test and tail suspension test on Swiss albino mice. The anti-depressant activity of the seeds of Zanthoxylum armatum was assessed using Chronic Unpredictable Mild-Stress (CUMS) induced depression in mice.Methods: The animals were treated with the methanolic extract of seeds of Zanthoxylum armatum orally at two doses of 100, 200mg/kg body weight for eight days after CUMS induced depression in mice. The results demonstrate that Methanolic extract of seeds of Zanthoxylum armatum has got anti-depressant potential.Results: The study showed that the extract of Zanthoxylum armatum had significant antidepressant activity. Microsoft Excel was used to calculate the mean ± SEM and one-way ANOVA followed by a turkey multiple comparison test was used to analyze the results. The seed extract presented significant antidepressant activity in mice (p